A non-destructive method for analyzing the overall wettability of batteries
By performing specific assembly and first charging tests on lithium-ion batteries, the wetting coefficient K is calculated using voltage disturbance, the accuracy and reliability of electrolyte wetting evaluation in the prior art are solved, and efficient and low-cost overall wetting testing of the battery is achieved.
Patent Information
- Application Number
- CN202510121334.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-26
AI Technical Summary
The prior art is difficult to accurately and reliably judge the overall wetting properties of lithium-ion battery electrolytes, and often requires complex equipment and cumbersome operations, which are costly and are not conducive to actual production operations.
By baking the electrolyte and assembling it into a battery with the positive electrode sheet, the lithium metal negative electrode sheet and the separator, a specific first-time charging test method is used to calculate the wetting coefficient K using the voltage disturbance in the early stage of the first charging to evaluate the overall wetting of the battery.
Accurate and reliable evaluation of the overall wettability of the battery is achieved, simplified the testing process, reduced costs, improved testing efficiency, and eliminated the need to disassemble the battery's individual test pole or diaphragm.
Smart Images

Figure CN119556161B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery testing and relates to a method for non-destructively analyzing the overall wettability of a battery. Background Art
[0002] Lithium-ion batteries (LIBs) have been widely used in electronic devices, electric vehicles (EVs), and grid energy storage, and the demand for lithium-ion batteries with higher energy density has been growing continuously. To this end, the industry has mainly conducted research on material systems and battery cell design. Among them, the use of thick electrodes to increase the compaction density and surface density of positive and negative electrodes, thereby reducing the number of electrode folds or layers, is an effective technical means. However, after adopting the design of thick electrodes, the battery cell process and performance will be affected, especially the problem of poor electrolyte wettability. Therefore, reliable judgment of electrolyte wettability is particularly important.
[0003] CN115586109A discloses a method and device for judging the wettability of lithium-ion battery pole pieces, comprising weighing the battery pole pieces to be tested and spreading them on a filter component; distributing a spray component, a filter component and a bottom support component vertically; during testing, controlling the spray component to spray electrolyte, and the electrolyte is sprayed from the spray component to the pole pieces on the filter component and finally reaches the bottom support component; weighing the tested battery pole pieces again; weighing the spray liquid on the bottom support component after the test, and judging the changes in weight multiple times to determine the infiltration speed of the electrolyte.
[0004] CN115326961A discloses a method for evaluating the wettability of a lithium-ion battery electrode, comprising step S1, injecting an electrolyte containing LiFSI into a baked battery cell and then vacuum packaging to complete an aging process; step S2, disassembling the packaged battery obtained in S1 to obtain an electrode and completing a punching process to obtain a sample, treating the sample by infiltration and ultrasonic dispersion to obtain an electrolyte in the sample; step S3, filtering out a filtrate with a water-based filter membrane to test IC, and according to the FSI in the filtrate, - The electrolyte content in the sample is obtained by the concentration, and the obtained electrolyte content is compared with the theoretical value to evaluate the wettability of the lithium-ion battery electrode.
[0005] CN215004841U discloses a device for measuring the wettability of a diaphragm, comprising a power supply, a test slot and a voltage and time measuring part; the test slot comprises a clamping assembly and an electrolyte; a tension zone acting on the diaphragm is provided in the clamping assembly, and the diaphragm is clamped in the clamping assembly; when measuring the wettability of the diaphragm, the clamping assembly holding the diaphragm is immersed in the electrolyte; the voltage and time measuring part is connected to both ends of the test slot, electrically connected to the power supply, and used to measure and record the real-time voltage of the diaphragm and its corresponding time. Compared with the prior art, the test slot of the device simulates the setting of the diaphragm in the battery cell, the tension zone simulates the stress condition in the battery cell, and then the real-time voltage of the diaphragm and its corresponding time are tested by the measuring part to reflect the change of the wettability of the diaphragm over time, and then reflect the liquid absorption speed of the diaphragm, and quantitatively measure the wettability problem of the diaphragm.
[0006] The wettability of the electrolyte inside the battery is usually affected by the pole piece and the diaphragm. Therefore, in the above existing technical solutions, the general idea of judging the wettability is to test the weight and other properties of the pole piece or diaphragm before and after wetting, and then calculate or compare them. Therefore, a complex equipment system is often required and the operation is cumbersome and error-prone. At the same time, since the tested pole piece and diaphragm are not tested inside the battery, the results cannot reflect the actual wettability state inside the battery. For example, those weight change test schemes before and after wetting require a large cost investment, which is not conducive to operation in actual production of enterprises.
[0007] Therefore, there is still a need to develop a simple, accurate and reliable non-destructive method for testing the overall wettability of batteries. Summary of the invention
[0008] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for non-destructively analyzing the overall wettability of a battery, wherein the electrolyte is baked, and then assembled into a battery with a positive electrode, a lithium metal negative electrode and a diaphragm; the battery is left to stand with the positive electrode at the bottom and the negative electrode at the top; the battery after standing is charged for the first time, and the wettability coefficient K is calculated based on the voltage disturbance at the initial stage of the first charge to establish a relationship for the overall wettability of the battery. The present invention artificially amplifies the concentration polarization inside the battery through a specific battery assembly method and a specific first charge test method, and uses the voltage disturbance caused by the concentration polarization to characterize the wettability inside the battery, which can more accurately and comprehensively express the actual internal wettability state of the battery without the need to test the internal electrode or diaphragm separately. The method is simple and easy to implement, does not require complex testing equipment, and can effectively shorten the test cycle and improve the test efficiency.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a method for non-destructively analyzing the overall wettability of a battery, the method comprising:
[0011] The electrolyte is baked and then assembled with the positive electrode sheet, the lithium metal negative electrode sheet and the separator into a battery;
[0012] The battery is placed in a static state with the positive electrode at the bottom and the negative electrode at the top;
[0013] After the battery has been left to stand for the first time, charge it until the cut-off voltage is reached and calculate the wettability coefficient K according to the following formula: ; Wherein, η is the fluidity of the electrolyte, V is the injection volume of the electrolyte, j is the unit correction coefficient, t is the standing time, A is the area of the positive electrode sheet, U0 is the highest voltage within 30 seconds before the first charge, and U1 is the lowest voltage from U0 to the cut-off voltage during the first charge.
[0014] Usually, after the battery is assembled, its starting voltage is mainly related to the concentration polarization caused by the voltage of the electrode material itself, the wettability of the electrode material and the wettability of the diaphragm. When concentration polarization exists, the battery charging voltage will be higher than the actual voltage of the electrode material itself, and at the beginning of charging and discharging, there is often a process of rapid recovery to normal voltage changes. With this characteristic, the present invention proposes to amplify the difference in wettability inside the battery by artificially increasing concentration polarization, establish a connection with the voltage disturbance of the first charge, and thus evaluate the wettability inside the battery.
[0015] In order to increase the concentration polarization in the present invention: first, a specific battery assembly method is adopted, that is, the electrolyte needs to be baked to increase the concentration polarization. The electrolyte is baked at high temperature to increase the viscosity and concentration of the electrolyte to cause a greater concentration polarization, so that its macroscopic manifestation is a larger voltage difference. After a short period of high-temperature baking, the electrolyte can further enhance the Brownian motion of the molecules inside the electrolyte, making the solubility between the electrolyte and the solvent better and more uniform. Liquid injection after baking can further reduce the surface tension between the electrolyte and the inside of the particles, improve the wettability of the electrolyte, and make it easier for the electrolyte molecules to enter the interior of the electrode. Second, the present invention adopts a specific first charge test method, that is, the battery is left to stand with the positive electrode at the bottom and the negative electrode at the top before starting the test. In this way, when the battery is charged for the first time, the lithium ions inside the battery are released from the positive electrode and embedded in the negative electrode. Since the negative electrode is at the top and the positive electrode is at the bottom, the lithium ions need to overcome gravity and move from bottom to top. At this time, since the electrolyte has been baked at high temperature, the viscosity and concentration of the electrolyte are relatively large, and the resistance to the movement of lithium ions is relatively large. The voltage difference of the first charge will be more obvious, and the difference in wettability inside the battery can be more accurately and quantitatively characterized.
[0016] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0017] As a preferred technical solution of the present invention, the baking temperature is 40-60°C, for example, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, 58°C or 60°C, and the baking time is 5-60min, for example, 5min, 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min or 60min, but is not limited to the listed values, and other values not listed within the above numerical range are equally applicable.
[0018] In the present invention, the baking is to increase the viscosity and concentration of the electrolyte, and therefore the baking is preferably performed without sealing.
[0019] As a preferred technical solution of the present invention, the battery is a button battery. Preferably, the radius of the positive electrode sheet of the button battery is 7-9 mm, such as 7 mm, 7.2 mm, 7.4 mm, 7.6 mm, 7.8 mm, 8 mm, 8.2 mm, 8.4 mm, 8.6 mm, 8.8 mm or 9 mm, etc., but it is not limited to the listed values, and other values not listed in the above numerical range are also applicable.
[0020] In the research and development stage of lithium-ion batteries, button cells (button batteries) are usually used to quickly simulate the actual capacity of a material or part of an electrode in a full-electric battery cell, and the method described in the present invention is very suitable for button cells.
[0021] It is understandable that in addition to the electrolyte, positive electrode, lithium metal negative electrode and separator, the battery may also contain other necessary structures or components, such as the battery also includes a battery shell and a filler, and the filler includes a gasket and / or a spring.
[0022] As a preferred technical solution of the present invention, the standing time is 5 to 120 min, for example, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min or 120 min, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0023] In the present invention, the purpose of the standing time is to achieve the infiltration of the electrolyte and ensure that the concentration polarization effect can be clearly reflected. Considering that there is a time difference before the battery is completed and put on the cabinet for testing, the standing time must not be equal to 0, but if the standing time is too short, it may not meet the purpose of the present invention to expand the concentration polarization.
[0024] As a preferred technical solution of the present invention, the first charge rate is 0.05-0.33C, such as 0.05C, 0.08C, 0.1C, 0.12C, 0.14C, 0.16C, 0.18C, 0.2C, 0.23C, 0.25C, 0.28C, 0.3C or 0.33C, preferably 0.05-0.15C, more preferably 0.08-0.12C. However, it is not limited to the listed values, and other values not listed in the above numerical range are also applicable.
[0025] In the present invention, a suitable rate should be selected for the first charge test. As the rate increases, the accuracy of the result tends to decrease. The best choice is to use a rate of 0.1C, which can effectively eliminate the influence of different impedances.
[0026] As a preferred technical solution of the present invention, when U0≤U1 and / or (U0-U1)<1, the difference of (U0-U1) in the formula is defined as 1.
[0027] Since the technical concept of the present invention is to amplify the concentration polarization, when performing specific battery assembly and specific testing according to the method, by selecting the appropriate electrolyte baking temperature, pole piece area and wetting time, the increased concentration polarization can ensure that U0>U1, that is, when U0>U1, the smaller the difference, the larger the K value, and the better the wettability. If for those cases where U0≤U1 and / or (U0-U1)<1, it means that the wettability is excellent, so the difference is 1 for calculation. In order to make the difference in K value more obvious, it is ensured that the value of (U0-U1) is>1, and it is preferred that U0 and U1 are calculated in units of mV (millivolts).
[0028] As a preferred technical solution of the present invention, η=viscosity of the electrolyte×molar concentration of the electrolyte in the electrolyte×porosity of the diaphragm; η=0.12~0.54, for example, 0.12, 0.15, 0.18, 0.2, 0.22, 0.24, 0.27, 0.3, 0.32, 0.35, 0.38, 0.4, 0.41, 0.43, 0.46, 0.48, 0.49, 0.5, 0.52, 0.53 or 0.54, etc., but are not limited to the listed values, and other values not listed within the above numerical range are equally applicable.
[0029] It should be noted that in the formula, the fluidity η does not require units, and its numerical value is related to the viscosity of the electrolyte and the porosity of the diaphragm, and the viscosity of the electrolyte is affected by the baking temperature of the electrolyte. Therefore, when comparing the K value, the viscosity of the electrolyte in each battery, the porosity of the diaphragm, the injection amount of the electrolyte, the molar concentration of the electrolyte in the electrolyte, the time the battery is stationary, the area of the positive electrode sheet and other factors should be kept consistent, and each calculation should be performed in the same unit to effectively quantitatively measure the wettability of the battery. In other words, in a certain battery system, the value of η is fixed, and a larger η value will make the wettability coefficient have a more obvious difference.
[0030] As a preferred technical solution of the present invention, the viscosity of the electrolyte is 0.46~0.52Pa·s, such as 0.46Pa·s, 0.47Pa·s, 0.48Pa·s, 0.49Pa·s, 0.5Pa·s, 0.51Pa·s or 0.52Pa·s, etc.; the injection volume of the electrolyte is 10~150μL, such as 10μL, 15μL, 20μL, 25μL, 30μL, 35μL, 40μL, 45μL, 50μL , 55μL, 60μL, 65μL, 70μL, 80μL, 90μL, 100μL, 110μL, 120μL, 130μL, 140μL or 150μL, etc., the porosity of the diaphragm is 40%~50%, for example, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49% or 50%, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0031] As a preferred technical solution of the present invention, the value of j is 1.
[0032] It should be noted that the wettability coefficient K calculated in the present invention is a scalar quantity without any specific unit restriction, that is, the unit of the unit correction coefficient j in the formula is also not fixed, and it is used to eliminate other units in the formula so that K is a dimensionless scalar quantity. For example, when η has no unit, such as the unit of V is μL (microliter), the unit of t is min (minute), and the unit of A is cm 2 (square centimeters), the units of U0 and U1 are mV (millivolts), and the unit of j is mV cm 2 ·min 1 / 2 μL -1; Even when η is substituted into the unit for calculation, it can be eliminated by changing the unit of j. As can be seen from the formula, the present invention can eliminate the remaining influencing factors inside the battery through the scalar wettability coefficient K of the battery. The present invention calculates the time period of static soaking after the battery is assembled, and then only obtains the internal wettability of the battery through the voltage change of the first charge. There is no need to pay attention to the voltage change of the battery during long-term static standing, which also greatly improves the test efficiency.
[0033] As a preferred technical solution of the present invention, the compaction density of the positive electrode material in the positive electrode sheet is 2-5 g / m 3 , for example 2g / m 3 , 2.3g / m 3 , 2.5g / m 3 , 2.8g / m 3 , 3g / m 3 3.3g / m 3 3.5g / m 3 3.8g / m 3 , 4g / m 3 4.3g / m 3 4.5g / m 3 4.8g / m 3 or 5g / m 3 The area of the positive electrode sheet is 1-10 mm 2 , for example 1mm 2 , 2mm 2 , 3mm 2 , 4mm 2 , 5mm 2 、6mm 2 , 7mm 2 , 8mm 2 , 9mm 2 or 10mm 2 etc., but are not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0034] It should also be noted that the method of the present invention does not restrict the composition and content of the electrolyte, the material of the diaphragm, and the material selection and composition ratio of the positive electrode material, binder and conductive agent. All the options that have been used in the field of lithium-ion batteries are applicable to the present invention.
[0035] Illustratively, the positive electrode material of the positive electrode sheet includes lithium cobalt oxide or a ternary material; and the separator includes a PP film or glass fiber.
[0036] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0037] The present invention artificially amplifies the concentration polarization inside the battery through a specific battery assembly method and a specific test method, and quantitatively analyzes the voltage drop at the initial stage of the first charge to characterize the wettability inside the battery, which can more accurately and comprehensively express the overall wettability of the battery. The method of the present invention does not require disassembling the battery to separately test the wettability of the internal pole piece or diaphragm, does not require complex testing equipment, is simple and easy to operate, has low cost, and has a fast response time. It can effectively shorten the test cycle, greatly improve efficiency, and is conducive to accelerating the research and development and iteration of high-energy positive electrode materials and batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the voltage curve of the button cell obtained in Example 1 at 3.9-4.05V for the first charge.
[0039] Figure 2 This is the voltage curve of the button cell obtained in Example 5 at 3.9-4.05V for the first charge.
[0040] Figure 3 This is the voltage curve of the button cell obtained in Example 7 at 3.9-4.05V for the first charge. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0042] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.
[0043] Example 1
[0044] This embodiment provides a method for non-destructively analyzing the overall wettability of a battery, the method comprising:
[0045] Provide positive electrode sheet, negative electrode sheet, separator and electrolyte. Among them, the compaction density is selected to be 2.5g / m 3 3.3g / m 3 and 4.1g / m 3 The lithium cobalt oxide materials are denoted as A, B and C, and are used as positive electrode materials respectively; SP is selected as the conductive agent, PVDF as the binder, and NMP as the dispersant. The quantitative materials are weighed according to the mass proportions of the positive electrode material, conductive agent, dispersant and binder being 94.5%, 1%, 2% and 2.5% respectively. First, the binder is prepared into a glue solution in a certain amount of solvent, and then the positive electrode material and the conductive agent are added and uniformly put into a blender for uniform mixing to make a uniform positive electrode slurry. The prepared positive electrode slurry is evenly coated on aluminum foil to make three positive electrode sheets, and the area of each positive electrode sheet is 1.5386cm 2; The negative electrode sheets are uniformly made of metal lithium sheets; there are two diaphragms, both of which are glass fibers with a porosity of 40%; the battery shell is a Kejing CR2035 battery shell (including a positive electrode shell and a negative electrode shell), the filler is Kejing's shrapnel and gasket, and the electrolyte is a commercial lithium cobalt oxide electrolyte (Shenzhen Xinzhoubang Technology, model LBC450A21), and the molar concentration of the electrolyte in the electrolyte is 1.2 mol / L.
[0046] After the electrolyte was baked at 45°C for 1h, the viscosity of the electrolyte was 0.49Pa·s. At this time, it was calculated that η=viscosity of the electrolyte×molar concentration of the electrolyte in the electrolyte×porosity of the diaphragm=0.24 (no unit required), and then the positive electrode shell, spring, gasket, positive electrode sheet, injection of 50μL electrolyte, diaphragm, injection of 50μL electrolyte, diaphragm, injection of 50μL electrolyte, negative electrode sheet and negative electrode shell were stacked and assembled in sequence and injected with liquid, and then packaged with a sealing machine, the packaging pressure was 850kg, and the time was 5s, to obtain three button batteries;
[0047] The button battery was put on the cabinet for testing, and a 5V2A power supply was used to test the control unit. The positive pole of the button battery was kept at the bottom and the negative pole was at the top. After standing for 30 minutes, it was charged for the first time at a rate of 0.1C. Figure 1 As shown, the highest voltage U0 within 30 seconds before the first charge is recorded, and the lowest voltage U1 from U0 to the cut-off voltage;
[0048] Substitute into the formula to calculate the wettability coefficient , the results are shown in Table 1.
[0049] Example 2
[0050] This embodiment provides a method for non-destructively analyzing the overall wettability of a battery. The method adjusts the baking temperature from 45° C. to 35° C. Except for the above, other conditions are exactly the same as those in Example 1.
[0051] Example 3
[0052] This embodiment provides a method for non-destructively analyzing the overall wettability of a battery. The method adjusts the baking temperature from 45° C. to 60° C. Except for the above, other conditions are exactly the same as those in Example 1.
[0053] Example 4
[0054] This embodiment provides a method for non-destructively analyzing the overall wettability of a battery. The method adjusts the standing time of the button-type battery after being placed on the cabinet from 30 minutes to 5 minutes. Except for the above, other conditions are exactly the same as those in Embodiment 1.
[0055] Example 5
[0056] This embodiment provides a method for non-destructively analyzing the overall wettability of a battery. The method adjusts the standing time of the button-type battery after being placed on the cabinet from 30 minutes to 120 minutes. Except for the above, other conditions are exactly the same as those in Embodiment 1.
[0057] Example 6
[0058] This embodiment provides a method for non-destructively analyzing the overall wettability of a battery. In the method, the injection volume of the electrolyte each time is adjusted from 50 μL to 10 μL. Except for the above, other conditions are exactly the same as those in Example 1.
[0059] Example 7
[0060] This embodiment provides a method for non-destructively analyzing the overall wettability of a battery. In the method, the injection volume of the electrolyte each time is adjusted from 50 μL to 150 μL. Except for the above, other conditions are exactly the same as those in Example 1.
[0061] Comparative Example 1
[0062] This comparative example provides a method for non-destructively analyzing the overall wettability of a battery. The method does not bake the electrolyte. Except for the above, other conditions are exactly the same as those in Example 1.
[0063] Comparative Example 2
[0064] This comparative example provides a method for non-destructively analyzing the overall wettability of a battery. The method places the battery at rest and performs the first charge test with the positive electrode on top and the negative electrode on the bottom. Except for the above, other conditions are exactly the same as those in Example 1.
[0065] Comparative Example 3
[0066] This comparative example provides a method for non-destructively analyzing the overall wettability of a battery. The method performs a first charging test on the battery immediately after it is loaded on the cabinet, and the standing time is about 1 second. Except for the above, other conditions are exactly the same as those in Example 1.
[0067]
[0068] Note: In Table 1, the unit of j in the formula for calculating K value is mV cm 2 ·min 1 / 2 μL -1 .
[0069] Figure 1 is the voltage curve of the button cell obtained in Example 1 at 3.9-4.05V for the first charge; Figure 1It can be seen that U1 of the three groups of materials A / B / C is less than U0. The battery corresponding to material A has the smallest voltage difference, which means it has the lowest concentration polarization. The calculation results in Table 1 show that the wettability coefficient K corresponding to material A is 1.31, the wettability coefficient K corresponding to material B is 0.15, and the wettability coefficient K corresponding to material C is 0.08; and under the same other conditions, the greater the compaction density of the same material itself, the worse its wettability should be, and the compaction density of the three lithium cobalt oxide materials is C>B>A, which means that its wettability is A>B>C, which is consistent with the numerical value of the wettability coefficient K, which illustrates the accuracy of the present invention.
[0070] Combined with the data in Table 1, by comparing Examples 1, 2, and 3 with Comparative Example 1, it is found that the baking temperature of the battery cell has a significant effect on η. Within a certain range, the higher the baking temperature, the larger the η value, resulting in a larger K value, that is, proper battery cell baking will amplify the voltage difference inside the battery, but too high a baking temperature will make the calculated wettability coefficient K less differentiated, which is not conducive to distinguishing between materials. For example, in Example 3, the K value of material B is 0.05, and the K value of material C is 0.03, the difference between the two is only 0.02, and the differentiation of the wettability results of the materials is reduced.
[0071] Figure 2 is the voltage curve of the button cell obtained in Example 5 at 3.9-4.05V for the first charge; Figure 2 It can be seen that among the three groups of materials, only material C with the largest compaction density has U1 less than U0. According to the wettability coefficient K, the wettability coefficient K corresponding to material A is 2.13, the wettability coefficient K corresponding to material B is 2.13, and the wettability coefficient K corresponding to material C is 0.005, indicating that material C has the worst wettability. Combining the data in Table 1, by comparing Examples 1, 4, and 5 with Comparative Example 3, it is found that as the value of the standing time t increases, the K value decreases. The appropriate extension of the standing time expands the voltage difference within the voltage. Too little standing time will reduce the voltage difference within the voltage, reduce the difference in wettability coefficients between different materials, and make it impossible to distinguish the wettability differences between materials. As shown in Comparative Example 3, the K values of materials A and B are both 11.7 at the shortest standing time, which is not enough to distinguish materials with different compaction densities. That is, in the present invention, standing time that is too long or too short will reduce the differentiation of wettability between materials.
[0072] Figure 3 is the voltage curve of the button cell obtained in Example 7 at 3.9-4.05V for the first charge; Figure 3It can be seen that U1 in the three groups of materials is greater than U0. According to the wettability coefficient K, the wettability coefficient K corresponding to material A is 12.81, the wettability coefficient K corresponding to material B is 12.81, and the wettability coefficient K corresponding to material C is 12.81, indicating that the wettability of materials ABC is relatively good. However, in combination with the data in Table 1, by comparing Example 1 with Examples 6 and 7, it is found that as the injection amount increases, the larger the V value, the larger the K value. At the same time, the increase in excessive injection amount also reduces the voltage difference within the voltage. For example, in Example 7, when the injection amount is too much, the K values of the three materials A / B / C are all 12.8, and it is impossible to compare and distinguish the wettability. That is, in the present invention, excessively increasing the electrolyte injection amount will reduce the differentiation of wettability between materials.
[0073] Combined with the data in Table 1, by comparing Example 1 with Comparative Example 2, it is found that changing the placement of the battery when it is at rest so that the positive electrode is on top will also reduce the internal voltage difference of the battery and reduce the wettability coefficient between different materials. The calculated wettability coefficients K are equal and the wettability differences between the materials cannot be distinguished.
[0074] To sum up, the method described in the embodiment of the present invention utilizes the relationship between the voltage drop in the initial stage of charging and the overall wettability of the battery, and provides a scheme for analyzing the overall wettability of the battery during the first charging test. This scheme can be used for real-time monitoring during the use of the battery cell, and at the same time, early warning is given to facilitate subsequent failure analysis. An indicator is proposed for the overall wettability test of the battery, and there is no need to perform separate wettability tests on the electrode or diaphragm, thereby improving the quality control efficiency of the battery testing section.
[0075] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0076] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0077] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for non-destructive analysis of the overall wettability of a battery, characterized in that: The method comprises: The electrolyte is baked and then assembled with the positive electrode sheet, the lithium metal negative electrode sheet and the separator into a battery; The battery is placed in a static state with the positive electrode at the bottom and the negative electrode at the top; After the battery has been left to stand for the first time, charge it until the cut-off voltage is reached and calculate the wettability coefficient K according to the following formula: ; Wherein, η is the fluidity of the electrolyte, V is the injection volume of the electrolyte, j is the unit correction coefficient, t is the standing time, A is the area of the positive electrode sheet, U0 is the highest voltage 30 seconds before the first charge, and U1 is the lowest voltage from U0 to the cut-off voltage during the first charge.
2. The method for non-destructive analysis of overall battery wettability according to claim 1, characterized in that: The baking temperature is 35-60° C. and the baking time is 5-60 min.
3. The method for non-destructive analysis of overall battery wettability according to claim 1, characterized in that: The battery is a button battery.
4. The method for non-destructive analysis of overall battery wettability according to claim 1, characterized in that: The standing time is 5 to 120 minutes.
5. The method for non-destructive analysis of overall battery wettability according to claim 1, characterized in that: The first charging rate is 0.05~0.33C.
6. The method for non-destructive analysis of overall battery wettability according to claim 1, characterized in that: When U0≤U1 and / or (U0-U1)<1, the difference value of (U0-U1) in the formula is defined as 1.
7. The method for non-destructive analysis of overall battery wettability according to claim 1, characterized in that: The value of j is 1.
8. The method for non-destructive analysis of overall battery wettability according to claim 1, characterized in that: η=viscosity of electrolyte × molar concentration of electrolyte in electrolyte × porosity of diaphragm; η=0.12~0.
54.
9. The method for nondestructive analysis of overall battery wettability according to claim 1 or 8, characterized in that: The viscosity of the electrolyte is 0.46-0.52 Pa·s; the injection volume of the electrolyte is 10-150 μL; and the porosity of the diaphragm is 40%-50%.
10. The method for non-destructive analysis of overall battery wettability according to claim 1, characterized in that: The compaction density of the positive electrode material in the positive electrode sheet is 2-5 g / m 3 The area of the positive electrode is 1~10cm 2 .
Citation Information
Patent Citations
Filling and activating method for flexible-packaging lithium ion battery
CN102646809A
Method for evaluating wettability of lithium ion battery pole piece
CN115326961A